Gender and heritage : performance, place and politics - Grahn, Wera, 1956-; Wilson, Ross J., 1981- (Abingdon, Oxon ; New York, NY : Routledge, 2018)
Gender and Heritage brings together a group of international scholars to examine the performance, place and politics of gender within heritage. Through a series of case studies, models and assessments, the significance of understanding and working with concepts of gender is demonstrated as a dynamic and reforming agenda. Demonstrating that gender has become an increasingly important area for heritage scholarship, the collection argues that it should also be recognised as a central structuring device within society and the location where a critical heritage studies can emerge. Drawing on contributions from around the world, this edited collection provides a range of innovative approaches to using gender as a mode of enquiry. From the politics of museum displays, the exploration of pedagogy, the role of local initiatives and the legal frameworks that structure representation, the volume's diversity and objectives represent a challenge for students, academics and professionals to rethink gender. Rather than featuring gender as an addition to wider discussions of heritage, this volume makes gender the focus of concern as a means of building a new agenda within the field. This volume, which addresses how we engage with gender and heritage in both practice and theory, is essential reading for scholars at all levels and should also serve as a useful guide for practitioners.
Introduction. -- The tyranny of the normal and the importance of being liminal / Ross J. Wilson -- Performance. -- Johanna, Moa and I'm every lesbian: gender, sexuality and class in Norrkoping's industrial landscape / Bodil Axelsson and David Ludvigsson -- Gender, heritage and changing traditions: Russian old believers in Romania / Cristina Clopot and Mairead Nic Craith -- Handicrafting gender: craft, performativity and cultural heritage / Anneli Palmskold and Johanna Rosenqvist -- Naturing gender and gendering nature in museums / Smilla Edeling -- Place. -- It's a man's world. Or is it? The 'Pilgrim fathers', religion, patriarchy, nationalism and tourism / Anna Scott -- The fleshyness of absence: the matter of absence in a feminist museology / Arndis Bergsdottir and Sigurjon Baldur Hafsteinsson -- Taller than the rest: the Three Dikgosi Monument, masculinity reloaded / Keletso G. Setlhabi -- Exploring identities through feminist pedagogy / Viv Golding -- Impasse or productive intersection? Learning to 'mess with genies' in collaborative heritage research relationships / Joni Lariat -- Politics. -- Transversal dances across time and space: feminist strategies for a critical heritage studies / Astrid von Rosen, Monica Sand and Marsha Meskimmon -- Gendering 'the other Germany': resistant and residual narratives on StauffenbergstraBe, Berlin / Joanne Sayner and Rhiannon Mason -- Gender and intangible heritage: illustrating the inter-disciplinary character of international law / Janet Blake -- Women of steel at the Sparrows Point Steel Mill, Baltimore, USA / Michelle L. Stefano -- 'Does it matter?' Relocating fragments of queer heritage in post-earthquake Christchurch / Andrew Gorman-Murray and Scott McKinnon -- Conclusion. -- The politics of heritage: how to achieve change / Wera Grahn.
Includes bibliographical references and index.
ARC
Parama
Keywords: Sex role -- History; Gender identity -- History; Sex role -- Social aspects; Gender identity -- Social aspects; Architecture; Sex role -- Political aspects; Gender identity -- Political aspects; Gender identity; Gender identity -- Political aspects; Gender identity -- Social aspects; Sex role; Sex role -- Political aspects; Sex role -- Social aspects